Engaging youths in skill development through network system wiring workshop in rural area - Hazilah Mad Kaidi; Norulhusna Ahmad; Nor Fazilah Mohd Hashim; Fatimah Salim; Mohd Nabil Muhtazaruddin; Nurul Aini Bani; Norliza Mohamed; Rafizah Musa; Siti Armiza Mohd Aris; Siti Zura A Jalil (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Nowadays, youths underuse their time, energy and creativity in a vast number of other activities, which lead to almost nothing in return. Thus, to fully utilise their huge potential of skills and abilities is by offering productive ways to attract young people in educational-related activities. This paper is presenting the community project on the network wiring system workshop that has been conducted for the young generation at Kg. Serting Ulu, Simpang Pertang Jempol, Negeri Sembilan, Malaysia. The aim of participating in this project is to deliver the knowledge base and develop skills in technology and engineering. In addition, it is also intended to develop interpersonal skills, communication and lifelong learning as well as to increase the ability of a young generation to generate a side income by venturing into entrepreneurship field. Participants in this network system wiring workshop were exposed to a multitude of basic installation and wiring techniques in which they were able to shape their personalities with the advantage of acquired technology and engineering skills. As a result, the return on investment (RoI) and social return on investment (SRoI) targets for the workshop can be achieved. It was conducted at a rural area named as Kampung Serting Ulu, Simpang Pertang Jempol, Negeri Sembilan, Malaysia.